Outcomes of Bronchial Artery Embolization for Life-Threatening Hemoptysis Secondary to Tuberculosis - Pei, Renguang (PLoS One, 2014)
OBJECTIVE: To appraise the immediate and long-term outcomes of bronchial arterial embolization for life-threatening hemoptysis secondary to tuberculosis. METHODS: 112 patients with life-threatening hemoptysis due to tuberculosis underwent bronchial artery embolization from January 2004 to February 2014. Life-threatening hemoptysis was defined as expectoration of at least 400 ml of blood in 24 hour. The median follow-up is 20 months, ranging from 2 to 52 months. RESULTS: The hemoptysis control rate was 86.6% at 14 days, 84.8% at 30 days, 78.6% at 240 days, 75.9% at 360 days, respectively. None of these characteristics, including gender, age and tuberculosis status, was significantly associated with immediate control of bleeding. Patients with active tuberculosis had a significantly longer recurrence-free duration than did patients with inactive tuberculosis (P = 0.040), which was further confirmed by Cox regression hazards model (P = 0.046). There was no spinal cord complication or mortality related to bronchial artery embolization. The most common complication was transient chest pain. CONCLUSION: Bronchial arterial embolization is an effective and safe technique in the management of life-threatening hemoptysis secondary to tuberculosis. Active tuberculosis may be associated with a lower rate of recurrence of hemoptysis.